CERVICAL RIPENING AND INDUCTION OF LABOUR WITH FOLEY'S CATHETER COMPARED TO OXYTOCIN - Elsadig, Abdallah H.; Hakeem, Mustafa A.; Abdul Hafeez, Abdul-Rahman (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 1 (2011), 2011)
Objective: The purpose of this study was to evaluate the effectiveness, efficiency, benefit, safety and maternal and fetal complications by using the Foley's urinary catheter size 20 versus oxytocin for preinduction ripening of the uterine cervix and induction of labour. Design: Prospective randomized clinical trial. Setting : Labour and delivery ward of Wad Medani Maternity Teaching Hospital. Methods: In the period from Jul. 2004 to Feb. 2005 Seventy  patients requiring induction of labour at term with a Bishop score of ≤ 5 were randomized to receive  Foley's catheter or oxytocin.  The two important indications for induction included in this study were prolonged pregnancy and pre-eclampsia. Results: In the Foley’s catheter group the balloon was expelled in 34/35 (97.14%). The Bishop score after expulsion of the balloon was 6 to 8. Nine cases (25.7%) had lower segment caesarean section compared to twenty cases (57.1%) in the oxytocin group. No maternal or neonatal morbidity or death in both groups .